Affliction - Banks, Russell, 1940- (HarperPerennial, 1990)
Wade Whitehouse is an improbable protagonist for a tragedy. A well-digger and policeman in a bleak New Hampshire town, he is a former high-school star gone to beer fat, a loner with a mean streak. Wade comes to loom in one's mind as a blue-collar American Everyman afflicted by the dark secret of the macho tradition.